Dakwah Nasionalisme KH. Much. Imam Chambali - Muhammad Nurhuda; Nurullina Wahidatus Salam (UIN Antasari Banjarmasin, 2022)
This article discusses the concept of da'wah nationalism in broadcasting Islamic values under the auspices of the Islamic boarding school developed by KH. Much. Imam Chambali. This study uses qualitative research with field research methods focused on the values of nationalism developed by KH. Much. Imam Chambali. The data collection instruments consist of interviews, documentation, and observations with the analysis technique of the Miles and Huberman model (data reduction, data presentation, and concluding). The results of the study illustrate that KH. Much. Imam Chambali carried out nationalism da'wah by planting and developing nationalism. How this is done can be seen clearly in three aspects. First, providing da'wah materials containing elements commemorating the services of heroes is expected to help foster a sense of nationalism. The second is an effort to inculcate an attitude of internal and inter-religious tolerance to create harmony. Third, acculturating the local language with its da'wah messages so that the da'wah message can be easily accepted by the community and as a tool to maintain nationalism in the era of globalization.